Asperspiropene A, a novel fungal metabolite as an inhibitor of cancer-associated mutant isocitrate dehydrogenase 1. Issue 6 (9th March 2017) - He, Yan; Zheng, Mengzhu; Li, Qin; Hu, Zhengxi; Zhu, Hucheng; Liu, Junjun; Wang, Jianping; Xue, Yongbo; Li, Hua; Zhang, Yonghui
Abstract : In silico screening of an in-house natural product database and confirmatory bioassays led to the identification of asperspiropene A (1 ) as an inhibitor of cancer-associated mutant IDH1. Abstract : In silico screening of an in-house natural product database and confirmatory bioassays led to the identification of asperspiropene A (1 ) as an inhibitor of cancer-associated mutant IDH1. Compound1, a meroterpenoid with a highly functionalized 1, 8-dioxaspiro[4.5]decane motif, showed potent ability to inhibit mutant IDH1 with inhibition constant ( K i ) values as low as 0.27 μM. The half effective concentration (EC50 ) of1 for reducing the cellular concentration of D2HG in HT1080 cells was 8.5 μM. Molecularly, treatment with1 led to reduced levels of the H3 K9me3 signal in the HT1080 cells. To the best of our knowledge, 1 is the first fungal metabolite reported to exhibit inhibitory activity against mutant IDH1.